Exploring the antimicrobial, antioxidant, and in vitro anti-inflammatory potential of Oxytropis microphylla (Pall.) DC. plant species of Ladakh region - Disket Zomba; Mushtaq Ahmad Dar; Rishikesh Singh; Daizy R. Batish; Shalinder Kaur (Discover Food)
Abstract Oxytropis microphylla, a plant native to the harsh climate of Ladakh, has garnered attention for its potential health benefits and ecological significance. This study explores the antioxidant, antimicrobial, and anti-inflammatory properties of O. microphylla extracts obtained from various solvents such as aqueous, ethyl acetate, methanol, and petroleum ether. Among the various extracts tested, the ethyl acetate extract demonstrated significantly higher scavenging activity (75%), compared to the aqueous, methanol, and petroleum ether extracts. The antimicrobial potential of O. microphylla indicated that the methanolic extract exhibited significant antimicrobial activity by effectively hindering the growth of Streptomyces scabiei and Rhodococcus fasciens. The respective growth inhibition zones were measured to be 90% and 77.5% at 400 µg mL−1 concentration compared with its positive control i.e., rifampicin, suggesting its potential use as a natural preservative. In vitro assays revealed that the anti-inflammatory effect of O. microphylla was comparable to that of standard anti-inflammatory agents. At 400 µg mL−1 concentration, methanol extract showed the maximum (~ 79%) inhibition rate, while the extracts of ethyl acetate and petroleum ether recorded a notable (~ 70%) inhibition. These findings not only underscore the therapeutic potential of the plant but also advocate for its conservation as a valuable resource in traditional medicine and sustainable practices in the Ladakh region. Further research is recommended to explore the isolation and characterization of different bioactive compounds present in O. microphylla which are responsible for these effects.